Exchange Rate Pass-Through in Spain - Murgasova, Zuzana (Washington, D.C. : International Monetary Fund, 1996)
This paper examines the factors underlying the stability of inflation observed following devaluations of the Spanish peseta, which took place during the 1992-93 Exchange Rate Mechanism (ERM) crisis. The long-run equilibrium relationships between the exchange rate and the aggregate price indices are estimated using the Johansen maximum likelihood-method. The short-run dynamics are obtained from error-correction models. The model is then simulated by calibrating changes in the exogenous variables to their actual values. The results indicate that the cost-push-up effect of devaluations may have been completely offset by determinants of the cyclical position of the economy and the low inflation rate in 1993-94 should not be viewed as unusual.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet